Survival and growth responses of Australian provenances of Eucalyptus tereticornis and Eucalyptus camaldulensis in soils of different salinities in North-West India - Dhanda, S.K.; Toky, O.P. (Indian Journal of Agroforestry, 2020)
Seeds of eight Australian provenances of Eucalyptus camaldulensis and Eucalyptus tereticornis, received from the CSIRO, Australia were tested on three saline soils (0.45, 2.16 and 3.97 dS m-1) in field conditions in Haryana located in north-west India. One local Indian seed source of Eucalyptus tereticornis was also included in the study for comparison. The growth of two years old plants varied significantly (P